Impact of International Trade Policies at Indonesia Malaysia Thailand Growth Triangle - Ahmad, Saari; Rashdan Sallehuddin, Mohd; bt Othman, Noraini (International Journal of Psychosocial Rehabilitation, 2020)
Purpose of Study: This article focus on the effectiveness of Malaysian government trade policies to assists the business activities in the IMT-GT region. The study is aimed to examine the level of helpfulness of the trade policies by the Malaysian government to assists the business activities in the region.Methodology: Adopting the stratified sampling method the data was collected from 300 respondents.Result: The findings clearly indicate that investment tax allowance, export credit refinancing, export credit insurance and reinvestment allowance are helpful to increase the business activities at the IMT-GT region. The business performance of the respondents are increasing annually.